2016
DOI: 10.1080/15377938.2016.1187235
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in the issuance of multiple traffic citations to motorists in a southern suburban police agency

Abstract: This study examines the issuance of multiple citations to single citations during traffic stops in a southern suburban community in the United States. The examination used logistic regression and simultaneously controlled for the ethnic dyad between the motorist and police officer. The results revealed Hispanics have the greatest odds of receiving multiple citations, followed by blacks, regardless of the ethnicity of the officer. The findings provide additional evidence the police are more punitive towards bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Previous research has also shown the utility of using the social conditioning model and illusory correlation as a theoretical explanation for police officer decision-making when it comes to citations, stop rates, search rates, frisks, and searches (Carroll and Gonzalez, 2014; Helfers, 2016; Renauer, 2012; Tillyer et al, 2019; Tillyer and Engel, 2013). However, only three studies considered consent searches or consent search requests.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also shown the utility of using the social conditioning model and illusory correlation as a theoretical explanation for police officer decision-making when it comes to citations, stop rates, search rates, frisks, and searches (Carroll and Gonzalez, 2014; Helfers, 2016; Renauer, 2012; Tillyer et al, 2019; Tillyer and Engel, 2013). However, only three studies considered consent searches or consent search requests.…”
Section: Introductionmentioning
confidence: 99%